Preliminary exploration of the role of parathyroid volume in predicting the efficacy of cinacalcet on secondary hyperparathyroidism - TANG Li; LIAO Chang-bin; Zhang Jia-li (Linchuang shenzangbing zazhi)
Objective To divide maintenance hemodialysis(MDH)patients with secondary hyperparathyroidism(SHPT)into various groups according to their parathyroid volumes,and preliminarily explore the role of parathyroid volume in predicting the efficacy of cinacalcet on SHPT by observing efficacy of cinacalcet in various groups.Methods Sixty-seven MHD patients with SHPT from Zigong Third People’s Hospital were selected and divided into three groups according to the maximum parathyroid volume:group A(parathyroid volume<500 mm~3,21 cases),group B(500 mm~3≤parathyroid volume<1 000 mm~3,23 cases),group C(parathyroid volume≥1 000 mm~3,23 cases).The initial dose of cinacalcet was 25 mg/day and increased gradually up to 100 mg/day to achieve the control goal covering the intact parathyroid hormone(iPTH)levels(150～300 pg/mL).The main observation index was iPTH compliance rate(150～300 pg/mL),and the secondary observation index was the rate of iPTH decline more than 30%.The changes in serum iPTH,corrected calcium and serum phosphorus were observed during the follow-up period of 24 weeks.Results One patient in group B fell off,and three in group C.The remaining patients were followed up for 24 weeks.There were no significant differences in baseline age,gender,calcium and phosphorus levels between the three groups.The baseline dialysis age of patients in group C was significantly longer than that in group A and B,with statistically significance.The levels of iPTH in the three groups before treatment were statistically different.After 24 weeks of treatment,the levels of serum calcium and serum iPTH in the three groups were significantly declined(P<0.05).The proportions of iPTH decreased by more than 30% in the three groups were high,with no statistically significant differences between the three groups.The iPTH compliance rate was 81% in group A,45.5% in group B and 10% in group C(P<0.05).In this study,29 of 63 patients met the standard of iPTH.Multiple regression analysis indicated that the maximum parathyroid volume before treatment and the pre-treatment iPTH were independent predictors of whether iPTH complied with the standard.Conclusions Cinacalcet had good efficacy in the treatment of SHPT in hemodialysis patients.Baseline maximum parathyroid volume and iPTH are independent predictors of iPTH compliance.